ANALYSIS OF SYMBOLS IN ENRICO CASAROSA’S LUCA ANIMATED MOVIE - Titis Setyabudi; Ledy Agustina (Literature and Literacy, 2024)
This research focuses on analyzing symbols in a film with the aim of understanding the meaning and function of these symbols. The research method used is qualitative and refers to the theory developed by Charles Sanders Peirce. The data collection process was carried out through in-depth observation of the symbolic elements in the films that were the object of research. A qualitative approach provides the opportunity for researchers to holistically understand the context and significance of these symbols in the film narrative. Thus, this research aims to provide an in-depth understanding of the role and meaning of symbols in a cinematic context and how these symbols contribute to the audience's experience in capturing the messages and stories conveyed by films.This research was aimed to explain the symbol and meaning in Enrico Casarosa's animated film Luca (2021) and to describe the function of symbols in the film. There were five symbols found in the film; Vespa represented freedom, friendship and solidarity; Sea and land represented the zone of comfort but limited and challenging life; Umbrella represented the identity add protection; Trophy represented victory; Sea monster represented fear and prejudice.